(untitled) (Aporte Santiaguino, 2024)
The aim of this study is to assess the bacterial growth time within biofilms in drinking water pipes. By simulating distribution networks at a scale level, bacteria were sampled, cultured, and quantified on plates over a 28-day period using various materials. The results underscore the dynamics of biofilm formation and bacterial growth. Following the initiation of the distribution network simulator, the formation of the biofilm and bacterial growth on the inner surfaces of the pipes was observed. Quantitative values were contingent upon the time and operational conditions of the simulator. After collecting and validating the data in the laboratory, it was concluded that bacterial growth within biofilms occurs within a 5-day operational period of the simulator, revealing temporal changes. Furthermore, the presence of aerobic bacteria such as Escherichia Coli and Staphylococcus Aureus.